Integration of Polymer Synthesis and Self‐Assembly for Controlled Periodicity and Photonic Properties. (18th September 2020) - Zhang, Ruimeng; Qiang, Zhe; Wang, Muzhou
Abstract: Materials chemistry and self‐assembly properties are usually treated separately, largely limiting the real‐time control of their nanostructures and resulting macroscopic properties in advanced self‐assembled materials. This study shows a model system that integrates synthesis and self‐assembly to achieve controlled periodicity and photonic properties in block copolymers (BCPs) at defined locations. First, the BCP thin films containing a pre‐dissolved photo‐initiator are swollen with monomer vapors. Upon exposure to UV light, the photoreaction synthesizes homopolymers within the film, which simultaneously blend with the BCPs and modify the periodicity in the exposed regions. This technique is successfully adapted to cylindrical polystyrene‐ b ‐polyisoprene‐ b ‐polystyrene and lamellar polystyrene‐ b ‐poly(2‐vinyl pyridine) BCP thin films. This capability is especially useful in the practical application of photonic crystals, where it is shown that the stop band position of polystyrene‐ b ‐quaternized‐poly(2‐vinyl pyridine) photonic gel films can be successfully modulated in situ. A large‐scale pattern is then fabricated by using a photomask. This study provides a model system for integrating materials synthesis and self‐assembly to achieve spatially defined control over structural periodicity and macroscopic properties in self‐assembled materials. Abstract : An in‐film photo‐polymerization method, integrating conventional photo‐controlled radical polymerization and a solvent annealing process, is presented to achieve in situ periodicity control in block copolymer (BCP) thin films. One of the promising applications is to tune the stop band position of BCP‐based 1D photonic gel films. The key advantage of this method is a one‐step hierarchical patterning through local exposure of UV light.